Application of mesoporous SBA-15 silica functionalized with 4-amino-2-mercaptopyrimidine for the adsorption of Cu(II), Zn(II), Cd(II), Ni(II), and Pb(II) from water - Jorgetto, Alexandre de Oliveira [UNESP]; Pereira, Silvana Pontes; Vieira da Silva, Rafael Innocenti [UNESP]; Saeki, Margarida Juri [UNESP]; Utrera Martines, Marco Antonio; Pedrosa, Valber de Albuquerque [UNESP]; Castro, Gustavo Rocha de [UNESP] (Slovensko Kemijsko Drustvo, 2015)
This work reports the sol-gel synthesis of an SBA-15 silica and its functionalization with 4-amino-2-mercaptopyrimidine to perform adsorption of metal species from aqueous media. The functionalization of the material was confirmed using FTIR and specific surface area measurements. The final material was tested through batch experiments to uncover its adsorptive properties toward the adsorption of Cu(II), Cd(II), Zn(II), Pb(II), and Ni(II). Contact time and pH conditions were investigated, and the material presented slow adsorption kinetics, which was best described by the pseudo- second order model. In addition, at pH 5-6, the adsorption of the metal ions was favored. Under optimized conditions, the material had its maximum adsorption capacities determined for all metal species studied, and the obtained values were 13.0 mu mol g(-1) for Zn(II), 12.3 mu mol g(-1) for Cu(II), 3.45 mu mol g(-1) for Ni(II), 2.45 mu mol g(-1) for Pb(II), and 0.60 mu mol g(-1) for Cd( II). The capacity differences between each metal ion were discussed in terms of their ionic radii and Person's soft/hard acids/bases concept.
Keywords: Adsorption; Mesoporous SBA-15 silica; Solid-phase extraction; Toxic metal; Organofunctionalization; 4-amino-2-mercaptopyrimidine